Pengembangan Desain Pelatihan Guru Berbasis Online: Penerapan Discovery Learning dalam Merdeka Belajar - Dimas Ario Sumilih; Firdaus W. Suhaeb; Atma Ras; Ernawati S. Kaseng; Mubarak Dahlan (Universitas Negeri Makassar, 2023)
Sekolah/madrasah as learning institutions must always update and innovate to provide the best learning and learning experiences for students. Discovery learning strategies and technology with the optimization of analytical, critical, and creative thinking can be one solution. Teachers, as the main pillar and spearhead of education, face difficulties in integrating this approach into their daily learning process. Therefore, it is urgent for teachers to participate in education and training designed with online-based development so that it reaches across geographical boundaries throughout Indonesia. The implementation of this community service is carried out by cooperating with an online education and training platform developed by the E-Guru.ID organizing institution. The implementation of this activity is carried out by taking an online-based method, which includes mentoring activities, interactive discussions, and assignments. The three methods are carried out online or online (in the network) through telegram groups and Zoom Meetings. Through the development of this online-based teacher training activity design, development strategies and discovery learning technology can contribute positively to the development of educational quality. Trainees can understand and apply the concepts of analytical, critical, and creative thinking in the context of independent learning.